Settlement at Cape Tobin (Scoresby Sund outpost), Greenland 1930 : Bopladsen ved Kap Tobin (Scoresby Sunds forpost), Grønland 1930 - Petersen, Sofie (University of Southern California Digital Library (USC.DL), 2015)
Settlement at Cape Tobin (Scoresby Sund outpost), Greenland 1930